Market orientation, innovation and performance of takaful business in Malaysia - Norizan Remli
It is recognized that the Islamic insurance industry, both globally and in Malaysia, is growing rapidly. Yet, despite this growth, the low penetration rate become major problem facing by the Takaful operators as opposed to the conventional Insurance companies. Even though various Islamic products and services available in the market, it does not fully contribute to increase the demand of the Muslims which dominating the population in Malaysia. Based on this reality, it is to be found of interest to examine whether marketing strategy and innovation influence the performance of Takaful business in Malaysia. Thus, this study attempts to achieve three objectives. First is to identify the performance of Takaful business in Malaysia. Second is to examine the relationship between market orientation, innovation and performance of Takaful business in Malaysia. Third is to investigate the mediating effect of innovation between market orientation and performance of Takaful business in Malaysia. Various relevant literatures were reviewed until a conceptual framework of the relationship between market orientation, innovation and organizational performance was produced. In order to achieve the research objectives, Marketing Department staff of six (6) composite Takaful Operators in Malaysia was selected by stratified disproportionate random sampling method approach to involve in this study. A total of 162 questionnaires were distributed and 111 responded in which they were analyzed. Overall, the research findings showed that the performance of Takaful business in Malaysia was at the moderate level. Based on the regression analyses, the result showed that positive relationship between market orientation, innovation and performance of Takaful business in Malaysia was existed. Empirically, the result indicated that innovation mediated the market orientation and performance of Takaful business relationship. The results of this study have provided a significant contribution to the Takaful operators to improve performance and sustain competitive advantage either from the theoretical or the empirical aspects.